Corporate Governance and Disclosure of Sharia Compliance: An Insight Based On Aaoifi Standards - Andraeny, Dita (IAIN Surakarta, 2021)
The objective of this study is to examine the effect of size and the frequency of meeting of Sharia Supervisory Board, audit committee, and auditor’s reputation on the disclosure of sharia compliance based on AAOIFI standard. The secondary data of this study was the annual report of 10 Islamic Commercial Banks in Indonesia from 2016 to 2018. Purposive sampling was used in selecting the data. While multiple linear regression was used for data analysis. The results of the study conclude that the size of the Sharia Supervisory Board has a positive and significant effect the on disclosure of sharia compliance based on the AAOIFI standard. On the contrary, the frequency of meeting of the Sharia Supervisory Board, audit committee, and auditor’s reputation have no significant effect on the disclosure of sharia compliance.